Correction: Evaluation of Whatman FTA cards for the preservation of yellow fever virus RNA for use in molecular diagnostics - Davis, Emily H.; Velez, Jason O.; Russell, Brandy J.; Basile, A. Jane; Brault, Aaron C.; Hughes, Holly R. (PLoS neglected tropical diseases, 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0010487.].